Conceptualizing and measuring citizens’ preferences for democracy: taking stock of three decades of research in a fragmented field - König, Pascal; Siewert, Markus B.; Ackermann, Kathrin (Comparative political studies, 2022)
Research dealing with citizens’ preferences for different conceptions of democracy has grown and diversified greatly. This has resulted in a highly fragmented field in which empirical evidence cannot easily be integrated into a consistent larger picture. This systematic review takes stock of this research to uncover the roots of existing inconsistencies and to show how future research can avoid them. It maps three decades of research regarding conceptualizations and measurement approaches that have been chosen to study citizens’ preferences for democracy. By systematically carving out the variation in the chosen approaches, the review shows why existing research can hardly add up to a clear diagnosis regarding what kind of democracy citizens prefer. A critical discussion based on this review highlights that cumulative research will require a stronger conceptual and methodological integration between different strands in the literature.
Gesehen am 26.01.2022